2018
DOI: 10.1093/mnras/sty2576
|View full text |Cite
|
Sign up to set email alerts
|

The CGM and IGM at z ∼ 5: metal budget and physical connection

Abstract: We present further results of a survey for absorption line systems in the spectra of four high redshift quasars (5.79 ≤ z em ≤ 6.13) obtained with the ESO Very Large Telescope X-Shooter. We identify 36 C iv and 7 Si iv systems with a ≥ 5σ significance. The highest redshift C iv and Si iv absorbers identified in this work are at z = 5.80738 ± 0.00017 and z = 5.77495 ± 0.00038, respectively. We compute the comoving mass density of Si iv (Ω Si iv ) and find that it evolves from Ω Si iv = 4.3 +2.1 −2.1 ×10 −9 at <… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 78 publications
(112 reference statements)
14
51
2
Order By: Relevance
“…This limiting column density allows them to study the identified SiIV population across the column density range [12.5, 14.0] over the full redshift path of their survey. In addition, Codoreanu et al (2018) show that the fiducial configuration in García et al (2017b) at z = 5.6 is compatible with the SiIV observations.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…This limiting column density allows them to study the identified SiIV population across the column density range [12.5, 14.0] over the full redshift path of their survey. In addition, Codoreanu et al (2018) show that the fiducial configuration in García et al (2017b) at z = 5.6 is compatible with the SiIV observations.…”
Section: Introductionsupporting
confidence: 80%
“…The calculated CDDFs are always below the observed values, and for high column densities, there is a clear departure from the fitting functions provided by D' Odorico et al (2013). Nonetheless, the synthetic CDDFs have a closer match with the observational values from Codoreanu et al (2018), in particular at high column densities. It is worth noting that Bosman et al (2017) data are just upper limits for the CIV-CDDF at 6.2 < z < 7.0, nevertheless the computed values in this test are significantly underrepresented.…”
Section: Change In the Normalization Of Hm12supporting
confidence: 55%
See 3 more Smart Citations